Integration Of Aswaja An Nahdliyah At MI Elpist Temanggung - Faizah; Ghaida Muthmainnah; Nayla Putri Mulyani (Jurnal Ilmu Pendidikan dan Sains Islam Interdisipliner, 2026)
Integration of Aswaja An-Nahdliyah values in Islamic Elementary School has become an increasingly important necessity amid the challenges posed by social and cultural developments and the flow of information that have the potential to influence students’ character. Madrasahs not only serve as institutions that transmit knowledge but are also responsible for shaping a moderate, tolerant, just, and balanced religious character in accordance with the principles of Ahlussunnah wal Jamaah An-Nahdliyah. This study aims to describe the implementation of the integration of Aswaja An-Nahdliyah values in the educational program at MI Elpist. The study employs a qualitative approach with data collection techniques including in-depth interviews, non-participant observation, and document analysis. Data were analyzed descriptively through the processes of data reduction, data presentation, and drawing conclusions. The results of the study indicate that the integrated Aswaja An-Nahdliyah values include tawasuth (moderation), tawazun (balance), ta’addul (justice), and tasamuh (tolerance). The integration of these values is manifested in the madrasah curriculum, the learning process through teaching approaches, methods, and strategies, the development of local content, and the cultivation of noble character in daily life within the madrasah environment. This implementation contributes to shaping students’ character to be religious, moderate, and of noble character in accordance with the values of Aswaja An-Nahdliyah.